NEGOTIATING POWER BETWEEN LEADING MALE AND FEMALE CHARACTERS IN TOY STORY 4 MOVIE - Farhanita, Farhanita; Kurniawan, Muhammad Hafiz (Universitas Islam Sumatera Utara (UISU), 2024)
This research investigates the negotiation of power between leading male and female characters in the movie Toy Story 4, focusing specifically on conversations involving two or more participants taking turns to express their opinions and reach an agreement. The study aims to examine how the female character Bo Peep is represented through negotiation analysis and to demonstrate her power using a functional-semantic approach (Systemic Functional Linguistics, SFL). The analysis centers on Bo Peep's power dynamics in her interactions with Woody. The research employs a qualitative descriptive method, with data collection focusing on conversations and the analysis of clauses. Data are analyzed using negotiation theory and concepts of women's representation. The study identifies 371 moves and instances in the timeframe of 37:06 to 01:06:41 minutes. The analysis emphasizes exchanges involving goods and services and interruptions, classifying data into categories of Mood, speech function, and exchange structure. Regarding the representation of power, the research identifies instances of power-over, power-to, and power-with.